Serious games, interaction and simulation : 6th International Conference, SGAMES 2016, Porto, Portugal, June 16-17, 2016, Revised selected papers /: 6th International Conference, SGAMES 2016, Porto, Portugal, June 16-17, 2016, Revised selected papers. (2017) - Unknown
No abstract available